Dynamical properties for a mixed Fermi accelerator model - Tavares, Danila F.; Araujo, A. D.; Leonel, Edson D. [UNESP]; Costa Filho, R. N. (Elsevier, 2013)
The behavior of the decay of velocity in a semi-dissipative one-dimensional Fermi accelerator model is considered. Two different kinds of dissipative forces were considered: (i) F-v and; (ii) F-v2. We prove the decay of velocity is linear for (i) and exponential for (ii). During the decay, the particles move along specific corridors which are constructed by the borders of the stable manifolds of saddle points. These corridors organize themselves in a very complicated way in the phase space leading the basin of attraction of the sinks to be seemingly of fractal type. © 2013 Elsevier B.V. All rights reserved.
Keywords: Decay of energy; Fermi map; Manifolds; Basin of attraction; Dissipative forces; Dynamical properties; Fractal type; Saddle point; Stable manifold; Automobile engine manifolds; Physics; Phase space methods